Sampling Escherichia coli and Total Coliforms using Stainless Steel Suction Lysimeters. Issue 1 (4th February 2013) - Cey, Edwin E.
Abstract : Methods for monitoring fecal indicator bacteria in soil pore water are needed to improve characterization of bacterial fate and transport in the vadose zone. Laboratory experiments were conducted using commercially available stainless steel suction lysimeters to assess their capability for sampling total coliform (TC) and Escherichia coli (EC) indicator bacteria. The lysimeters were placed in a liquid‐filled tank containing either wastewater effluent or bacteria‐free solution. During initial sampling, concentrations for both TC and EC were reduced by up to 3‐log (i.e., 1000‐fold) compared to wastewater input concentrations. Bacterial retention rates in the lysimeters decreased to values of approximately 0.5–1.5 log with repeated sampling and during subsequent sampling events. After placing the samplers in essentially bacteria free water, continued detections of TC and EC suggested a memory effect, but concentrations generally returned to within 1.0‐log of the input concentration after two or three samples were collected. The results indicate that stainless steel lysimeters can provide a reliable method for semi‐quantitative enumeration of fecal bacteria indicators in soil pore water.